Impact of monopolar TURP, bipolar TURP and photoselective vaporization of prostate for enlarged prostate on erectile function. Issue 1 (1st August 2017) - Vasudeva, Pawan; Kumar, Niraj; Kumar, Anup; Kumar, Gaurav; Patel, Mikir; Gupta, Pankaj
Abstract : Objectives: To compare monopolar transurethral resection of the prostate (TURP), bipolar TURP and photoselective vaporization of the prostate (PVP) by 120‐W GreenLight laser with regard to the impact on International Index of Erectile Function (IIEF)‐5 score in patients presenting with lower urinary tract symptoms (LUTS) secondary to prostate >80 mL. Methods: Between April 2012 and March 2015, 110 patients who satisfied eligibility criteria were divided into three groups according to surgical modality adopted to treat benign prostatic enlargement. Preoperative, perioperative, and follow‐up data were collected. The three groups were as follows: group A, monopolar TURP; group B, bipolar TURP; and group C, PVP. Results: The baseline characteristics of the three groups were similar. All the perioperative parameters were significantly favorable in group C compared with the other two groups, except for mean operative time, which was significantly higher in group C. International Prostate Symptom Score, postvoid residual urine, maximum flow rate and quality of life score had significant and similar improvement during follow up in all three groups. Also, prostate volume reduced significantly in all three groups following surgery, but it remained significantly higher in group C patients compared with groups A and B. Mean IIEF‐5 score was similar between the three groups at baseline and during each of the follow‐up visits. Groups A, B and C had declines of 3.27% ( P = 0.34), 2.68% ( P = 0.40) and 3.36% ( P = 0.35), respectively, in mean IIEF‐5 score at 12‐month follow up compared with baseline. Conclusions: Monopolar TURP, bipolar TURP and PVP by 120‐W GreenLight laser for prostate size >80 mL do not have a significant impact on IIEF‐5 score at 12‐month follow up.